Feasibility and usefulness of self-assessment of bleeding in patients with haematological malignancies, and the association between platelet count and bleeding. - Stanworth, S; Dyer, C; Casbard, A; Murphy, M (2006)
BACKGROUND AND OBJECTIVES: The aim of this study was to evaluate the collection of daily prospective information about bleeding outcomes in patients with thrombocytopenia, including information obtained by patient self-assessment. MATERIALS AND METHODS: Consecutive patients with haematological malignancies were enrolled in a study of bleeding data collection during the period of thrombocytopenia. A short educational session and information sheet was designed for self-assessment. Platelet counts and all transfusions were recorded daily. Bleeding scores were translated into World Health Organization (WHO) bleeding grades. RESULTS: Nineteen patients were included in the study. Four-hundred and ten days of thrombocytopenia were eligible for assessment of bleeds. Self-assessment was feasible, as defined by the total proportion of days on which self-assessment was completed (70%, 288 thrombocytopenic days). There was 86% agreement between bleeding data collected by self-assessment and by medical examination using a structured assessment form. Examples of discrepancies included the duration of petechiae/bruises and the reporting of minor bleeding. There was no evidence for an association between patients' morning platelet count and daily WHO bleeding grade. The incidences of WHO grade 1 and grade 2 bleeding on days with platelet counts < or = 10 x 10(9)/l, 11-20 x 10(9)/l, and > 20 x 10(9)/l were similar and did not reveal higher rates of bleeding at lower counts. CONCLUSIONS: Patient self-assessment can help to support comprehensive daily prospective monitoring of bleeding, specifically facilitating data collection following hospital discharge. The discrepancies between self-assessment and medical examination highlight the need to develop a validated international assessment tool. The association among platelet count, risk of bleeding and role of prophylactic platelet transfusions needs further evaluation in larger prospective trials.